Domestic, family, and gender-based violence against women: a literature review for youth and adult literacy education (Brazilian Journal of Health Research, 2025)
Introduction: This study addresses domestic, family, and gender-based violence against women, while also discussing related topics. Objective: The aim of this work is to support the development of didactic materials to complement the literacy education of youth and adults, explaining why national and international efforts are specifically directed at protecting women. Methods: This is a narrative literature review with a qualitative approach. The research was conducted non-systematically using the SciELO Brazil database and the Regional Portal of the Virtual Health Library (VHL). The following descriptors were used: “direito mulher brasil” (women’s rights Brazil); “violência doméstica familiar” (domestic family violence); “violência gênero mulher” (gender-based violence against women); and “violência mulher saúde” (violence against women and health). Results: Violence against women is often rooted in gender stereotypes and socially prescribed roles that dictate ideal behaviors for women and men. Reading documents concerning women’s rights — such as laws, treaties, conventions, and protocols – is essential to understanding the public policies developed to address this serious social issue. Conclusion: Much remains to be done to bring about a subjective and structural transformation of Brazilian culture, as machismo, sexism, discrimination, and misogyny continue to persist in daily life, and even more pervasively on social media.
Keywords: Domestic violence; Family violence; Gender-based violence